Liturgie en geloofsvorming. : ’n Kort verkenning - Wepener, Cas (Stellenbosch Theological Journal, 2023)
The relation between liturgical action and faith formation is the theme of this article. By means of a literature study this relation is explored and critically reflected upon. The literature scrutinised in this regard include liturgical-, practical theological- and cultural anthropological sources. It is argued that there is indeed a relationship between liturgical practices and faith formation, however, this formation can be of a positive and negative, depending on the quality of the liturgical practice. Therefore, it is critical to often revisit the theme of liturgy and faith formation and simultaneously critically scrutinize the quality of the lived liturgical practice of individuals and communities.